2015
DOI: 10.3174/ajnr.a4260
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Quantitative Susceptibility Mapping for the Diagnosis of Parkinson Disease

Abstract: BACKGROUND AND PURPOSE:Quantitative susceptibility mapping allows overcoming several nonlocal restrictions of susceptibilityweighted and phase imaging and enables quantification of magnetic susceptibility. We compared the diagnostic accuracy of quantitative susceptibility mapping and R2* (1/T2*) mapping to discriminate between patients with Parkinson disease and controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
120
2
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(141 citation statements)
references
References 46 publications
15
120
2
4
Order By: Relevance
“…Susceptibility weighted imaging at 3 Tesla has also been able to detect absence of nigrosomes in PD (Schwarz et al, 2014). Susceptibility mapping has shown increased magnetic susceptibility in the substantia nigra, consistent with increased iron content in PD (Loftipour et al, 2012; Murakami et al, 2015). Susceptibility mapping in PD patients has also shown improved imaging of the subthalamic nucleus and globus pallidus internus, both important regions for neurosurgical placement of electrodes for DBS (Liu, T. et al, 2013).…”
Section: Neuroimaging Of Pdmentioning
confidence: 81%
“…Susceptibility weighted imaging at 3 Tesla has also been able to detect absence of nigrosomes in PD (Schwarz et al, 2014). Susceptibility mapping has shown increased magnetic susceptibility in the substantia nigra, consistent with increased iron content in PD (Loftipour et al, 2012; Murakami et al, 2015). Susceptibility mapping in PD patients has also shown improved imaging of the subthalamic nucleus and globus pallidus internus, both important regions for neurosurgical placement of electrodes for DBS (Liu, T. et al, 2013).…”
Section: Neuroimaging Of Pdmentioning
confidence: 81%
“…These can be better observed in susceptibility maps than in simultaneously acquired R 2 * maps (Du et al, 2015;Murakami et al, 2015). This points towards either using multi-echo protocols covering a range of echo times up to 30ms, which will be sufficiently robust to compute R 2 * and susceptibility maps of deep gray matter regions, or single echo acquisitions with a TE~15-20ms and low BW to maximize SNR, and be able to compute susceptibility maps.…”
Section: Study Of Neurodegenerative Diseases and Agingmentioning
confidence: 94%
“…QSM has been actively applied to study the brains of PD patients (128,129), demonstrating greater sensitivity than R2* in identifying increased nigral iron in PD patients as compared to healthy controls (130-135). The voxel-based morphology analysis by Du et al (132) elegantly demonstrates selective SNc iron increase in perfect concordance with post mortem histology, underscoring the potential of QSM as a biophysical marker for therapeutic effects in clinical trials.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%
“…Devos, et al have recently reported very encouraging results showing that DFP improves PD motor performance and reduces nigral R2* values on GRE MRI, suggesting that DFP can be the first disease-modifying therapy for PD (127). Because QSM is superior to R2* for evaluating nigral iron (131,132,134,135,145), an important potential application of QSM in PD is to measure DFP's effectiveness of target-engagement in clinical trials.…”
Section: Clinical Applications Enabled By Qsm Biometal Imagingmentioning
confidence: 99%